Oseltamivir PK/PD Modeling and Simulation to Evaluate Treatment Strategies against Influenza-Pneumococcus Coinfection - Boianelli, Alessandro; Sharma-Chawla, Niharika; Bruder, Dunja; Hernandez-Vargas, Esteban A. (Frontiers in Cellular and Infection Microbiology, 2016)
Influenza pandemics and seasonal outbreaks have shown the potential of Influenza A virus 4 (IAV) to enhance susceptibility to secondary infection with the bacterial pathogen Streptococcus 5 pneumoniae (Sp). The high morbidity and mortality rate revealed the poor efficacy of antiviral 6 drugs and vaccines to fight IAV infections. Currently, the most effective treatment for IAV is 7 represented by antiviral neuraminidase inhibitors. Among them, the most frequently stockpiled is 8 Oseltamivir which reduces viral release and transmission. However, effectiveness of Oseltamivir 9 is compromised by the emergence of resistant IAV strains and secondary Sp coinfection. To date, 10 little attention has been given to evaluate how Oseltamivir treatment strategies alter Influenza 11 viral infection in presence of Sp coinfection and a resistant IAV strain emergence. 12 In this paper we investigate the efficacy of current approved Oseltamivir treatment regimens 13 using a computational approach. Our numerical results suggest that the curative regimen (75 mg) 14 may yield 47% of antiviral efficacy and 9% of antibacterial efficacy. An increment in dose to 150 15 mg (pandemic regimen) may increase the antiviral efficacy to 49% and the antibacterial efficacy 16 to 16%. The choice to decrease the intake frequency to once per day is not recommended due to 17 significant reduction in both antiviral and antibacterial efficacy. We also observe that the treatment 18 duration of 10 days may not provide a clear improvement on the antiviral and antibacterial efficacy 19 compared to 5 days. All together, our in silico study reveals the success and pitfalls of Oseltamivir 20 strategies within IAV-Sp coinfection and calls for testing the validity in clinical trials.